2009
DOI: 10.1103/physreve.79.016103
|View full text |Cite
|
Sign up to set email alerts
|

Multifactor analysis of multiscaling in volatility return intervals

Abstract: We study the volatility time series of 1137 most traded stocks in the US stock markets for the two-year period 2001-02 and analyze their return intervals τ , which are time intervals between volatilities above a given threshold q. We explore the probability density function of τ , P q (τ ), assuming a stretched exponential function, P q (τ ) ∼ e −τ γ . We find that the exponent γ depends on the threshold in the range between q = 1 and 6 standard deviations of the volatility. This finding supports the multiscal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 41 publications
(66 reference statements)
2
28
0
Order By: Relevance
“…The main statistical properties of the FPT are the functional form of its probability distribution p.`/ and its average length h`i. Empirical studies have reported a variety of forms for the probability distribution of FPT, including (1) pure exponential for random uncorrelated processes [2], (2) stretched exponential forms for a diverse group of natural and social complex systems ranging from neuron firing [3], climate fluctuations [4], or heartbeat dynamics [5], to Internet traffic [6,7] and stock market activity [8,9]; and (3) power-law form for certain on-off intermittency processes related to nonlinear electronic circuits [10] and anomalous diffusion [11][12][13][14]. Such diverse behavior is traditionally attributed to the specifics of the individual system.…”
Section: Introductionmentioning
confidence: 99%
“…The main statistical properties of the FPT are the functional form of its probability distribution p.`/ and its average length h`i. Empirical studies have reported a variety of forms for the probability distribution of FPT, including (1) pure exponential for random uncorrelated processes [2], (2) stretched exponential forms for a diverse group of natural and social complex systems ranging from neuron firing [3], climate fluctuations [4], or heartbeat dynamics [5], to Internet traffic [6,7] and stock market activity [8,9]; and (3) power-law form for certain on-off intermittency processes related to nonlinear electronic circuits [10] and anomalous diffusion [11][12][13][14]. Such diverse behavior is traditionally attributed to the specifics of the individual system.…”
Section: Introductionmentioning
confidence: 99%
“…11), 15), 36) In after earthquake data, we note that the max amplitude varies in a very huge field. Therefore we test the relation between H and the max amplitude.…”
Section: Long-term Memory and Dependence On Max Amplitudementioning
confidence: 99%
“…This result does not satisfy the linear correlation function β = 1−H as seen in financial data and human interaction data. 35), 36) Therefore there must be some differences between the seismic noise data and others, e.g. some assumptions needed for the relation of β = 1 − H might not be fulfilled.…”
Section: Long-term Memory and Dependence On Max Amplitudementioning
confidence: 99%
See 2 more Smart Citations